Energy Storage and Release of Class I and Class II Rocks - Xing, Yan; Gao, Feng; Zhang, Zhizhen; Zheng, Wenqi (Energies (Basel), 2023)
As underground excavations become deeper, violent rock failures associated with the sudden release of elastic energy become more prevalent, threatening the safety of workers and construction equipment. It is important to figure out the energy-related failure mechanisms of rocks. However, the energy evolution across the complete deformation of different types of rocks and the effect of high confinement on energy storage and release are not well understood in the literature. In this study, a series of cyclic triaxial compression tests were conducted for Class I and Class II rocks to investigate the confinement-dependent characteristics of energy evolution. The results showed that three types of energy evolution were identified as the rock behavior changed from brittle to ductile. The energy storage limit was linearly enhanced by confinement. The nonlinear increase in dissipated energy at peak stress with increasing confinement was suggested to indicate the start of the brittle–ductile transition. The post-peak fracturing process was characterized using the ratio of the local withdrawn elastic energy and fracture energy, and a novel energy-based index was proposed to quantify the failure intensity of the rock. This paper presents a complete investigation of the energy conversion characteristics of the rock, which may shed light on the failure mechanisms of violent rock failures in underground projects.